Thawing permafrost poses environmental threat to thousands of sites with legacy industrial contamination - Langer, Moritz; Schneider von Deimling, Thomas; Westermann, Sebastian; Rolph, Rebecca; Rutte, Ralph; Antonova, Sofia; Rachold, Volker; Schultz, Michael; Oehme, Alexander; Grosse, Guido (Nature Communications, 2023)
Industrial contaminants accumulated in Arctic permafrost regions have been largely neglected in existing climate impact analyses. Here we identify about 4500 industrial sites where potentially hazardous substances are actively handled or stored in the permafrost-dominated regions of the Arctic. Furthermore, we estimate that between 13,000 and 20,000 contaminated sites are related to these industrial sites. Ongoing climate warming will increase the risk of contamination and mobilization of toxic substances since about 1100 industrial sites and 3500 to 5200 contaminated sites located in regions of stable permafrost will start to thaw before the end of this century. This poses a serious environmental threat, which is exacerbated by climate change in the near future. To avoid future environmental hazards, reliable long-term planning strategies for industrial and contaminated sites are needed that take into account the impacts of cimate change.
Gesehen am 22.05.2023
Literaturverzeichnis: Seite 9-10